2015
DOI: 10.1589/jpts.27.571
|View full text |Cite
|
Sign up to set email alerts
|

The effect of foot position on erector spinae and gluteus maximus muscle activation during sit-to-stand performed by chronic stroke patients

Abstract: [Purpose] The aim of this study was to use surface electromyography (EMG) to investigate the effects of different foot positioning on bilateral erector spinae (ES) and gluteus maximus (GM) activation during sit-to-stand performed by individuals with stroke. [Subjects] Fifteen randomly selected participants with stroke were enrolled in this study. [Methods] All the participants were asked to perform sit-to-stand (STS) using three different strategies: (1) symmetric foot position, (2) unaffected foot placed behi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…It causes axial asymmetry with asymmetrical activation of the internal obliques on both sides, and the posture of sitting with the legs crossed for a long time may also cause cyanosis and scoliosis 6 ) . If the peripheral circulation does not function smoothly, the tissues or cells are starved of oxygen, resulting in organic change, but minimal stimulus following a posture change elicits a change in the peripheral circulation 5 , 7 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It causes axial asymmetry with asymmetrical activation of the internal obliques on both sides, and the posture of sitting with the legs crossed for a long time may also cause cyanosis and scoliosis 6 ) . If the peripheral circulation does not function smoothly, the tissues or cells are starved of oxygen, resulting in organic change, but minimal stimulus following a posture change elicits a change in the peripheral circulation 5 , 7 ) .…”
Section: Discussionmentioning
confidence: 99%
“…During exercises to get off from sitting, the focus should be on all three dimensions of balance, but during the exercises to sit down from a standing position, the focus should be on improving the mediolateral balance and the asymmetrical position of the legs (24). In addition, the placement of the paretic foot behind the non-paretic foot during STS will cause more activity on the paretic muscles when compared to the symmetrical position of the legs or the non-paretic foot placement behind (9). Meanwhile, the position of the asymmetric feet while standing up from a sitting position improves the static and dynamic postural balance in patients with stroke (17).…”
Section: Discussionmentioning
confidence: 99%
“…ty -In a study conducted by Tae-Heon Lee [12] Tibialis Anterior got activated prior to other muscles which may a mechanism to facilitatethe STS movement by compensating for the delayed activation of the TrA/ IO muscles. However, A study conducted by Inkyeong Nam [9] concluded that the activity of Erector Spinae was lesser on affected side whereas activity of GM was greater on affected side. Effect of cane was observed by Hu P-T [14] in his study.…”
Section: Characteristics Of Emg Analysis :Onset Time Of Activi-mentioning
confidence: 98%
“…Sitto-stand (STS) begins in a safe sitting position and progresses to an unstable standing position, and it requires the lower extremity and trunk muscles to work together in harmony [5]. lower extremity and trunk muscle group activation during STS including one study on triceps muscle [9,10]. These studies gives us a brief picture about pattern of muscle activation, also which muscle activity is seen prior to the other muscle during the activity.…”
Section: Introductionmentioning
confidence: 99%